Fabrication of stable network-like gold nanostructures in solution and their assessment as efficient NIR-SERS platforms for organic pollutants detection. (April 2015) - Tira, Daniela-Simona; Potara, Monica; Astilean, Simion
Graphical abstract: Highlights: A facile and low-cost procedure to fabricate network-like gold nanostructures. Nanostructures show high stability in water and strong optical enhancing properties. Nanostructures can be readily used as NIR-SERS platforms for pollutants detection. Abstract: In this work we report a facile, rapid and low-cost procedure to fabricate network-like gold nanostructures and demonstrate their effectiveness as surface-enhanced Raman scattering (SERS) platforms for organic pollutants detection. The typical procedure starts with the preparation of standard colloidal gold nanoparticles solution followed by addition of zinc acetate which induces formation of novel and useful morphology for SERS substrates. The fabricated plasmonic nanoarchitectures exhibit high stability in water and strong optical enhancing properties in near-infrared (NIR). The NIR-SERS efficiency is assessed against two representative organic dyes, methylene blue and basic fuchsin. The study demonstrates that the as prepared platform can detect minute amounts of organic pollutants in aqueous solution with excitation at 785 nm diode laser line from a portable Raman spectrometer. The results are promising for integration in ultrasensitive optical devices for NIR-SERS detection of organic pollutants in watercourses.